Generalized Fractional Integral Inequalities for MT-Non-Convex and pq-Convex Functions - Wei Wang; Absar Ul Haq; Muhammad Shoaib Saleem; Muhammad Sajid Zahoor (Journal of Function Spaces)
Fractional integral inequalities have a wide range of applications in pure and applied mathematics. In the present research, we establish generalized fractional integral inequalities for MT-non-convex functions and pq-convex functions. Our results extended many inequalities already existing in the literature.